Norbornane-based nucleoside and nucleotide analogues locked in North conformation - Dejmek, Milan; Šála, Michal; Hřebabecký, Hubert; Dračínský, Martin; Procházková, Eliška; Chalupská, Dominika; Klíma, Martin; Plačková, Pavla; Hájek, Miroslav; Andrei, Graciela; Naesens, Lieve; Leyssen, Pieter; et al. (Bioorganic & medicinal chemistry, 2015)
We report on the synthesis of novel conformationally locked nucleoside and nucleotide derivatives, which are structurally closely related to clinically used antivirals such as didanosine and abacavir. As a suitable conformationally rigid substitute of the sugar/pseudosugar ring allowing a permanent stabilization of the nucleoside in North conformation we employed bicyclo[2.2.1]heptane (norbornane) substituted in the bridgehead position with a hydroxymethyl group and in the C-3 position with a nucleobase. Prepared nucleoside derivatives were also converted into appropriate phosphoramidate prodrugs (ProTides) in order to increase delivery of the compounds in the cells. All target compounds were evaluated in a broad antiviral and cytostatic assay panel.
Keywords: stereoizomerie; Carbocyclic nucleosides; Humans; PI4KIIα; Norbornane; Nucleosides; norbornany; nukleosidy; Purines; lidé; Antiviral; nukleotidy; Stereoisomerism; Nucleotides; antivirové látky; konformace nukleové kyseliny; Antiviral Agents; Nucleic Acid Conformation; Norbornanes